2015
DOI: 10.1523/jneurosci.0583-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Differential fMRI Activation Patterns to Noxious Heat and Tactile Stimuli in the Primate Spinal Cord

Abstract: Mesoscale local functional organizations of the primate spinal cord are largely unknown. Using high-resolution fMRI at 9.4 T, we identified distinct interhorn and intersegment fMRI activation patterns to tactile versus nociceptive heat stimulation of digits in lightly anesthetized monkeys. Within a spinal segment, 8 Hz vibrotactile stimuli elicited predominantly fMRI activations in the middle part of ipsilateral dorsal horn (iDH), along with significantly weaker activations in ipsilateral (iVH) and contralater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 52 publications
8
26
0
Order By: Relevance
“…At the subject level, no significant localization of the activity to the left or right hemicord was present, and at the group level, the activity for the painful stimulus was more evenly distributed across the right and left hemicords while the activity for the warm stimulus was localized more to the left hemicord. The absence of lateralization of the activity to the ipsilateral hemicord has been reported in previous SC fMRI studies using noxious thermal stimulation in humans (Geuter and Buchel, 2013; Summers et al, 2010) and non-human primates (Yang et al, 2015) and likely reflects the underlying complexity of SC sensory processing. The interneuronal networks within the dorsal horn not only relay sensory information to higher centers (i.e., brainstem and thalamus) but also actively integrate and modulate the sensory signals within the SC (Willis and Westlund, 1997).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…At the subject level, no significant localization of the activity to the left or right hemicord was present, and at the group level, the activity for the painful stimulus was more evenly distributed across the right and left hemicords while the activity for the warm stimulus was localized more to the left hemicord. The absence of lateralization of the activity to the ipsilateral hemicord has been reported in previous SC fMRI studies using noxious thermal stimulation in humans (Geuter and Buchel, 2013; Summers et al, 2010) and non-human primates (Yang et al, 2015) and likely reflects the underlying complexity of SC sensory processing. The interneuronal networks within the dorsal horn not only relay sensory information to higher centers (i.e., brainstem and thalamus) but also actively integrate and modulate the sensory signals within the SC (Willis and Westlund, 1997).…”
Section: Discussionmentioning
confidence: 53%
“…To date, several independent groups have used fMRI to study SC processing in both animals and humans using thermal (Brooks et al, 2012; Cadotte et al, 2012; Cahill and Stroman, 2011; Khan and Stroman, 2015; Nash et al, 2013; Summers et al, 2010; Yang et al, 2015), chemical (Malisza and Stroman, 2002; Porszasz et al, 1997), and electrical (Endo et al, 2008; Lilja et al, 2006; Zhao et al, 2009) experimental pain paradigms. Moreover, some studies have even demonstrated supraspinal influences on SC nociceptive processing (Dobek et al, 2014; Eippert et al, 2009; Geuter and Buchel, 2013; Sprenger et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this review we will solely focus on the human spinal imaging literature, although exciting advances have been made with regard to spinal imaging in rats (e.g. Lawrence et al, 2004;Lilja et al, 2006;Zhao et al, 2009), cats (Cohen-Adad et al, 2009a), and very recently also in monkeys (Chen et al, 2015;Yang et al, 2015), where finegrained sensory processing patterns were investigated as well as changes in restingstate connectivity due to spinal cord injury. It will be exciting to see how these approaches develop, especially when considering their application in tandem with other techniques such as two-photon imaging (Johanssen & Helmchen, 2013) or optogenetics (Montgomery et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These results highlight the fact that the overall cross-horn activation patterns to tactile and nociceptive heat inputs are more complex than have previously been recognized. Instead of functioning as a simple motor output horn, ventral horns (primarily ipsilateral) are also engaged in the processing of both tactile and nociceptive inputs (52). This finding is significant because the ventral horn activation to unilateral painful stimuli may be explained by the engagement of local spinal reflex circuitry, but the similar responses to innocuous tactile stimuli suggest that the ventral horn likely plays a larger role than just mediating simple pain-signal reflex activity (53).…”
Section: Detection Of Distinct Fmri Responses In Spinal Cord To Noxiomentioning
confidence: 99%
“…Orange, green and magenta color cones indicate statistically different responses between touch and nociceptive heat. Modified from (52). …”
Section: Figurementioning
confidence: 99%